Insight into influence of degradation metabolism of Firmicutes on the microstructure of anthracite coal - Yuewu Wang; Bingjun Liu; Sheng Xue; Yang Yang; Jian Chen; Jingbei Zhang; Chunshan Zheng; Tianyao Zhou (Energy Exploration & Exploitation)
Promoting the permeability of deep, low-permeability coal seams through biological means is currently a research hotspot for enhancing the efficiency of coalbed methane extraction. In this study, we selected anthracite coal from Sihe Mine for microbial anaerobic degradation culture experiments. The effects of adding functional microorganisms on the microstructure of anthracite coal were analyzed by high-throughput sequencing of samples before and after the cultivation and microcharacterization experiments of coal samples. The results showed that the maximum methane migration during the period of biodegradation reached 0.640 mL/g coal, and the cumulative migration of the whole cycle was as high as 1.318 mL/g coal. 16S rRNA high-throughput sequencing results indicated that the bacterial community structure had undergone significant succession after the biodegradation experiments, and that the Firmicutes represented by Bacillus(82.41% of the total) occupied the dominant niche. Metabolic pathway analysis based on Kyoto Encyclopedia of Genes and Genomes (KEGG) database showed that the degradation of aromatic compounds by microorganisms appeared to be significantly enhanced by the addition of nitrogen sources. Also, the relative abundance of a number of key metabolic enzyme genes capable of catalyzing the oxygen-containing functional groups into the structure of the coal molecule and the de-cyclization reaction were increased. Fourier Transform Infrared Spectrometer (FTIR) experiments revealed that biodegradation stimulated by nitrogen source reduced the aromaticity of coal by 59.62% and enhanced the hydroxyl functional group content by 1.822 times. Mercury pressure and low-temperature nitrogen adsorption experiments showed that the micropore pore volume of the treated coal decreased by 34.09%, and the macropore pore volume accounted for an increased 168.28%, with an average pore size increment of 60.72 nm. Therefore, the nitrogen source can stimulate Firmicutes on the degradation of polycyclic aromatic hydrocarbon and increase the content of oxygen-containing functional groups, which might promote the development of pores in coal and make the difficult-to-desorption methane migrates rapidly. This study investigated the effect of nitrogen source on the degradation of coal by Firmicutes. This will help improve the efficiency of gas extraction and ensure the safety of coal mine production.